A Sample-Sparing Multiplexed ADCP Assay - Butler, Audrey L.; Fallon, Jonathan K.; Alter, Galit (Frontiers in Immunology, 2019)
Antibodies serve as the primary correlate of protection following most clinically approved vaccines and are thought to confer protection in part through their ability to block (neutralize) infection. Increasingly, studies have shown that beyond their blocking activities, the ability of antibodies to leverage the innate immune response may serve a vital role in protection from infection. Specifically, antibodies can drive phagocytosis, complement activation, and cellular cytotoxicity by interacting with Fc-receptors found on all innate immune cells. Measuring the capacity of antibodies to induce these functions has become critical for the identification of correlates of protection in large-scale vaccine trials. Therefore, there is a growing need to develop robust, high throughput assays able to interrogate the functional capacity of innate immune recruiting antibodies. However, in many instances, only small sample volumes are available. Nevertheless, profiling antibody functions across many pathogen-associated antigens or across global intra-pathogen variants is in high demand, making sample sparing approaches to perform this antibody evaluation critical. Here we describe the development of an approach to interrogate the functional activity of antibodies in serum against up to 5 antigen targets simultaneously. A single bead-based cellular assay was adapted to accommodate 5 different fluorescently colored beads, allowing for the concurrent investigation of antibody responses directed against multiple antigens in a single well. The multiplexed assay was as sensitive, specific, and accurate as the single antigen assay and robustly able to assess functional differences mediated by antibodies across different samples. These findings show multiplexing allows for accurate and more efficient analysis of antibody-mediated antibody effector profiles.